Paired vehicle occupant analysis indicates age and crash severity moderate likelihood of higher severity injury in second row seated adults in frontal crashes. (April 2016) - Atkinson, T.; Gawarecki, L.; Tavakoli, M.
Highlights: Analysis of adult occupant pairs in frontal crashes indicates that the second row occupant is at a higher risk of injury when that occupant is the older of the pair. In age matched front and second row occupants, the likelihood of more severe injury in the second row increases as the crash severity increases. The risk level is moderated by crash severity such that injury to second row occupants will be more frequently observed in high severity crashes. These finding are similar to those in a recent study of crashes in Australia, demonstrating the broad nature of these findings. Abstract: The majority of advances in occupant protection systems for motor vehicle occupants have focused on occupants seated in the front row of the vehicle. Recent studies suggest that these systems have resulted in lower injury risk for front row occupants as compared to those in the second row. However, these findings are not universal. In addition, some of these findings result from analyses that compare groups of front and second row occupants exposed to dissimilar crash conditions, raising questions regarding whether they might reflect differences in the crash rather than the front and second row restraint systems. The current study examines factors associated with injury risk for pairs of right front seat and second row occupants in frontal crashes in the United States using paired data analysis techniques. These data indicate that the occupant seated in the front row frequently experiences the more severe injury in the pair, however there were no significant differences in the rate of occurrence of these events and events where the more severe injury occurs in the second row occupant of the pair. A logistic regression indicated that the likelihood of the more severe injury occurring in the second row seated occupant of the pair increased as crash severity increased, consistent with data from anatomic test dummy (ATD) tests. It also indicated that the second row occupant was more likely to have the more severe injury in the pair if that occupant was the older occupant of the pair. These findings suggest that occupant protection systems which focus on providing protection specifically for injuries experienced by older occupants in the second row in higher severity crash conditions might provide the greatest benefit.